PENGARUH KEMASAN PRODUK DAN RASA TERHADAP MINAT BELI YANG BERDAMPAK PADA KEPUTUSAN PEMBELIAN PELANGGAN MINUMAN ENERGI - Willy, Willy; Nurjanah, Siti (Jurnal Ilmu Manajemen, 2019)
This study aims to: Know and explain and evaluatethe effect of product packaging and taste on customer buying interests that have an impact on customer buying decisions; and knowing and explaining the influence of buying interest on buying energy drink customers. The variables in this study are product packaging and taste with buying interest as intervining variables and buying decisions as the dependent variable. This study uses a type of quantitative research. The population of this study were respondents who consumed energy drinks. The sample used amounted to 137 respondents using purposive sampling. The results showed that: product packaging and taste had a positive effect on customer buying interest; product packaging forms have a positive effect on customer buying decisions; product taste does not have a positive effect on buying interest and customer buying decisions.